HUBUNGAN LAMA KERJA, BAGIAN KERJA DAN PEMAKAIAN MASKER DENGAN SUSPEK DAN INFEKSI MYCOBACTERILM TUBERCULOSA (Studi di Balai Peneegahan dan Pengobatan Penyakit Paru Semarang Tahun 2003) - Didik . Suwarsono; Nurhayati . .; Sayono . . (Universitas Muhammadiyah Semarang, 2003)
ABSTRACT Background: Pulmonary Tuberculosis is still a public health problem, New cases is occurred 583.000 per year, and 140.000 of them died. Up to 2000, there were 69.771 suspects, 3.524 new cases. Of BTA (+), 124 reoccurrences and 1.806 BTA roentgen (+) in Central Java. This disease is caused by Mycobacterium tuberculosis that transmitted though the respiratory tract by droplet nuclei and dust. Health workers in BP4 is one of high risk group of this disease because face and service many patients everyday. This research is designed to analyze the correlation among job tenure and job division, and masker usage with suspect and infection of mycobacterium tuberculosis. Method: this explanatory research is used cross sectional design and survey approach. Population of study are all of the BP4 health workers. The independents variables are job tenure, job division, and masker usage, and the dependents are suspects and infection occurrence. Data analyzed statistically by Chi Square test at 5%o significant level. Results: there is not infected Berson in health workers of BP4 Semarang, and only 8,7% of the them are suspects. There is not correlation among job tenure,job, television, and masker usage with suspects. Conclusion: the suspect’s occurrence did not base ort job tenure, job division, and masker usage. Keyword: job tenure, job division, masker usage, pulmonary tuberculosis